2022
DOI: 10.1186/s12871-022-01711-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled double-blind study of dexmedetomidine on postoperative sleep quality in patients with endoscopic sinus surgery

Abstract: Background Postoperative sleep disorder is common and may cause aggravated postoperative pain, delirium, and poor prognosis. We accessed the effect of intraoperative intravenous dexmedetomidine on postoperative sleep quality in patients with endoscopic sinus surgery.  Methods This single-center, double-blind, placebo-controlled randomized clinical trial enrolled a total of 110 participants aged 18 years to 65 years who were scheduled to receive end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…After reviewing the full text of the remaining 52 potentially eligible articles, 21 were excluded because they were study protocols, one was a review, 15 had no PSG data, seven were not for surgical patients, one was not an adult study, one was not an RCT, and one had no control group. Five eligible studies were identified [13,14,[18][19][20]. The selection process is illustrated in Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the full text of the remaining 52 potentially eligible articles, 21 were excluded because they were study protocols, one was a review, 15 had no PSG data, seven were not for surgical patients, one was not an adult study, one was not an RCT, and one had no control group. Five eligible studies were identified [13,14,[18][19][20]. The selection process is illustrated in Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Compared to gamma-aminobutyric acid (GABA) agonists, DEX more closely resembles natural NREM sleep [8,9]. Several studies have reported favorable effects of DEX on sleep quality in patients after surgery or in the intensive care unit (ICU), as evaluated by objective tools, sleep questionnaires, or subjective assessments [10][11][12][13][14]. However, no meta-analysis of randomized controlled trials (RCTs) has focused on the effect of DEX on sleep quality in postoperative patients, and the optimal dosage and overall effect of DEX remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…6,11 This mechanism, in combination with its favorable effects on postsurgical inflammation, pain, and delirium, may improve postoperative sleep patterns. 6,7,11 Sleep disturbances after ambulatory procedures have also been documented; 4 however, the true incidence and severity are difficult to quantify given insufficient followup. We report the case of a 24-year-old man with a history of ASD, who experienced a propofol-induced exacerbation of an underlying sleep-onset disorder that did not recur with the primary use of dexmedetomidine during an outpatient procedure.…”
mentioning
confidence: 99%
“…1,2 Propofol exposure has been shown to impair sleep quality, [3][4][5] whereas similar effects have not been observed with dexmedetomidine administration. 6,7 Propofol-induced sleep disturbance may be related to circadian rhythm alterations at the level of the suprachiasmatic nuclei (SCN) and impaired melatonin production. 8 Circadian rhythm sleep-wake disorders are known to be common among patients with autism spectrum disorder (ASD).…”
mentioning
confidence: 99%
See 1 more Smart Citation